Discípulos de Rawls em busca de uma concepção cosmopolita de justiça distributiva internacional - Cepaluni, Gabriel [UNESP]; de SáGuimarães, Feliciano (FapUNIFESP (SciELO), 2010)
In this article, we make the argument that some of John Rawl's disciples, reflecting on the principles of international justice, have taken a position that is more consistent with the spirit of his A Theory of Justice than the author himself has. Scholars such as Charles Beitz and Thomas Pogge defend mechanisms of international distributive justice that seem to be more in line with the cosmopolitanism of the principle of difference that can be found within A Theory of Justice than are other efforts that Rawls himself made in his later work, more oriented toward international issues, The Law of Peoples. More specifically, we maintain that Pogge and Beitz developed more solid arguments (the relativization of the principle of the absolute sovereignty of States and international transfer of natural resources) for transporting the principle of difference into the international arena than what can be found within Rawls' proposal on the duty of aid in The Law of Peoples. We thereby demonstrate that Rawls' disciples are more faithful to the cosmopolitan spirit at the international level than he himself was, for three reasons: their belief in a world community of fellow citizens within an international institutional structure; the idea that the global production of collective resources should be redistributed through a principle of dense distribution and, finally, the notion that redistribution that can only be just insofar as it demands the moral reform of international institutions (International Monetary Fund, World Trade Organization, World Bank, principle of sovereignty etc.) in such a way as to improve the life conditions of world's poorest peoples. Thus, this article discusses the most progressive legacy of authors whom, in taking their inspiration from Rawls, developed arguments that were more adequate than his own for nourishing a cosmopolitan spirit within the international arena.
Rawls' disciples in search of a cosmopolitan conception of international distributive justice
Keywords: Distributive justice; Normative theories of international relations; Reforming international institutions